Prognostic biomarkers and their impact on treatment strategy selection for patients with advanced stages of oropharyngeal cancer - Rakhmanov, V.V.; Shponka, I.S. (Medicni Perspektivi, 2025)
The study of prognostic biomarkers is crucial for personalising and enhancing the effectiveness of oropharyngeal cancer treatment, as they help identify patients with aggressive disease progression and determine the optimal patient management strategy. Purpose: Analysis of the effectiveness of the use of biomarkers in the context of human papillomavirus status for predicting oncological events, functional outcomes to optimise treatment approaches for patients with advanced oropharyngeal cancer. The study examined the results of examination and treatment of 120 patients aged 37 to 80 years, of both sexes diagnosed with stage III-IV oropharyngeal cancer (T3-4N0-3M0-1). The clinical and morphological characteristics and the outcomes of histological and immunohistochemical analyses of biopsy and surgical samples were assessed. Human papillomavirus (HPV) status was determined using immunohistochemistry for the p16 oncoprotein. Statistical analysis was performed using R Commander (https://www.r-project.org/) and MedCalc Statistical Software trial version 22.030 (https://www.medcalc.org/), applying descriptive and analytical statistics, rank correlation, logistic regression, and receiver operating characteristic (ROC) analysis. In late stages of oropharyngeal cancer, increased expression of Cyclin D1 and epidermal growth factor receptor (EGFR) was significantly more common in HPV-negative cases compared to HPV-positive ones (p<0.05). HPV-negative tumours were associated with homozygous deletion cyclin dependent kinase inhibitor 2a gene (CDKN2A). The identification of biomarkers as prognostic criteria for different HPV statuses confirms their role in choosing a treatment strategy. Biomarkers like Ki-67 and homozygous deletion of CDKN2A were prognostic for metastasis, while Ki-67 and Cyclin D1 were linked to recurrence. EGFR showed the highest prognostic accuracy for predicting masticatory muscle trismus. Increased expression of Cyclin D1 and Ki-67 in late stages of oropharyngeal neoplasms correlated with combined treatment, increasing the odds by 4.42 times and 25%, respectively (p<0.05). Evaluation of biomarkers such as p16, EGFR, Cyclin D1, and Ki-67 provides essential information into disease prognosis and response to treatment, enabling risk stratification, tailored treatment planning, and the development of personalized strategies for managing advanced oropharyngeal cancer.